Protein Solubilization. (2nd May 2018) - Sathe, Shridhar K.; Zaffran, Valerie D.; Gupta, Sahil; Li, Tengfei
Abstract: To address the anticipated global need for increased protein supply for human nutrition, particularly for developing and underdeveloped regions, concerted efforts are required. Although animal proteins satisfy nutrition needs, they may not be acceptable to all consumers either due to their cost or dietary restrictions followed by the consumer. Soybean has served as a nonanimal protein source; however, alternative protein sources will need to be cultivated and explored in the future to satisfy anticipated increased global needs. To effectively utilize a food protein source, separation of proteins from the nonprotein components present in that source is often needed or desired. Such separation requires understanding of protein properties and interactions of the protein with its environment. In chemical separation processes, protein solubility is a critical property as it often governs protein preparation and utilization and is the focus of this review. Emphasis is on nontraditional protein sources.